Upaya Penurunan Nyeri Dismenore Melalui Edukasi Stretching Pada Santri Putri di Pondok Pesantren Tahfidz Al Mabrur - Prakasiwi, Sherkia Ichtiarsi; Khasanah, Umi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The incidence of dysmenorrhea in Central Java has reached 56%, this proves that the problem of dysmenorrhea cannot be considered trivial. In Semarang there are 2.11% - 3.1% of the number of women who experience dysmenorrhea who come to the obstetrics department, but there are still many dysmenorrhea patients who do not report. For sufferers of dysmenorrhea can limit women in their daily activities. Many female students are unable to carry out their activities, thus interfering with the Koran and worship activities. This causes the absence of female students to decrease. An understanding of menstruation is needed to be able to encourage adolescents who experience menstrual disorders to know and take the best attitude. Based on these conditions, this Community Service aims to reduce the level of dysmenorrhea pain in female students. The method used is counseling and education (demonstration) stretching to 56 female students. The result of this activity is a decrease in the level of dysmenorrhea pain, an increase in knowledge about the right treatment to reduce dysmenorrhea pain.